THE ABSOLUTE COMPETENCE OF THE JURISDICTION OF THE ADMINISTRATIVE COURT IN A DISPUTE WHOSE OBJECT IS A FICTIVE-POSITIVE KTUN - Francisca Romana Harjiyatni (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractBased on the Law on Administrative Court, the Administrative Court has the competence to examine and decide upon a dispute whose object is a fictive- negative decision (KTUN). After the enactment of the Law No. 30 of 2014 on Government Administration, the Administrative Court has the competence to examine and decide a dispute whose object is a fictive positive KTUN. The provision of the positive decision in the Law No. 30 of 2014 provides fairer legal protection to both procedural justice and substantive justice. However, the force power of the court to execute decision remains low. Consequently, a fair legal protection to the dispute of positive KTUN per the Law No. 30 of 2014 is not optimal.IntisariBerdasarkan UU PTUN, PTUN mempunyai kewenangan untuk memeriksa dan memutus sengketa yang obyeknya KTUN fiktif negatif. Setelah berlakunya UU No. 30 Tahun 2014 tentang Administrasi Pemerintahan, PTUN mempunyai kewenangan memeriksa dan memutus sengketa yang obyeknya KTUN fiktif positif. Ketentuan KTUN fiktif positif dalam UU No. 30 Tahun 2014 lebih memberikan perlindungan hukum yang adil baik keadilan prosedural maupun keadilan substansial, namun dalam hal daya paksa pelaksanaan masih rendah maka perlindungan hukum yang adil dalam sengketa KTUN fiktif positif berdasarkan UU No. 30 Tahun 2014 menjadi tidak optimal.